Weed Density and Dominant Weed Species in Malapari (Pongamia pinnata (L.) Pierre) Agroforestry - Endah Suhaendah; Benyamin Dendang (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2019)
The purpose of this study was to determine the weed density and the dominant species of weeds in Malapari (Pongamia pinnata (L). Pierre) agroforestry. The study was conducted in Patutrejo Village, Grabag District, Purworejo Regency. The method used is single plot method in malapari agroforestry, as a comparison of observations of weeds on empty land that is not planted. Weed sample collection was carried out by the quadratic method measuring 1 m x 1 m as many as 3 plots placed in malapari agroforestry and empty land diagonally. Observations were repeated 3 times so that there were 18 observation plots. The results showed that weed density in malapari agroforestry (29.95) was lower than empty land (54.17). The dominant species of weeds in both malapari agroforestry and empty land is Eulalia amaura (Buese) with Important Value Index (IVI) of 36.40 % and 43.39 %. This species is a pioneer weed and fast growing, so monitoring and control are needed so that the weed population is not economically disserve.Keywords: agroforestry, density, dominant, malapari, weed